Glycan dependent refolding activity of ER glucosyltransferase (UGGT) - Wang, Ning; Seko, Akira; Takeda, Yoichi; Ito, Yukishige (Biochimica et biophysica acta. General subjects, 2020)
In the endoplasmic reticulum (ER), folding of glycoproteins is assisted by a combined action of enzymes and chaperones that leads them to biologically functional structures. In this system, UDP-glucose:glycoprotein glucosyltransferase 1 (UGGT1) plays an essential role as the “folding sensor” by virtue of its ability to discriminate folding states of client glycoproteins. However, besides its transferase activity, whether UGGT1 possesses any chaperone activity that facilitates protein folding is yet to be addressed. We prepared oligomannose-type glycan modified RNase (M9GN2-RNase) by chemoenzymatic means using M9GN-oxazoline and glycan truncated RNase B and analyzed the effect of human UGGT1 (HUGT1) for refolding of the denatured M9GN2-RNase. Refolding was evaluated based on the RNase activity which was measured by the cleavage of the RNA substrate. HUGT1 slightly accelerated the folding of M9GN2-RNase and non-glycosylated RNase A as the same extent. However, HUGT1 remarkably accelerated the folding of M9GN2-RNase in the presence of UDP-Glc. In contrast, neither UDP nor UDP-Gal was effective in enhancing the folding. Additionally, an HUGT1 mutant which lacks the glucosyltransferase activity did not accelerate the protein folding of M9GN2-RNase. HUGT1has the ability to promote the refolding of denatured protein and the effect would be enhanced when HUGT1 tightly interacts with the client protein via glycan recognition. Our study provides a possibility that HUGT1 play a role not only in sensing the misfolded glycoprotein but also in promoting folding of glycoproteins in the endoplasmic reticulum glycoprotein quality control. [Display omitted] •The possibility that UGGT participates in the folding process of glycoprotein as a chaperone is yet to be addressed.•Human UGGT1 (HUGT1) accelerates the folding of the glycan modified RNase.•The refolding activity of HUGT1 is dependent on its glucose transfer activity.